Coronavirus Disease (COVID-19–SARS-CoV-2) and Nutrition: Is Infection in Italy Suggesting a Connection? - Cena, Hellas; Chieppa, Marcello (Frontiers in Immunology, 2020)
Novel coronavirus disease (COVID-19) was declared a global pandemic on March 11, 2020. The outbreak first occurred in Wuhan, Hubei, China, in December 2019 and hit Italy heavily in February 2020. Several countries are adopting complete or partial lockdown to contain the growth of COVID-19 infection. These measures may affect people's mental health and well-being but are necessary to avoid spreading the pandemic. There has been a gradual increase in studies exploring prevention and control measures, and we recommend paying close attention to nutrition, which may contribute to modulating some important consequences of COVID-19 infection, as such pro-inflammatory cytokine storm.